2014
DOI: 10.1186/2194-7899-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between past trauma, current social support, and loneliness in incarcerated populations

Abstract: BackgroundPrisoners are a vulnerable population with higher rates of trauma than community populations. Social support is important for both in–prison adjustment and post-release community re-entry. Loneliness, a related construct to social support, has been found to be associated with elevated rates of suicidal ideation and behavior, depression, and hopelessness in incarcerated populations.MethodsThis study explored the relationship of past physical, sexual, and crime-related trauma to current perceived socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
1
16
0
1
Order By: Relevance
“…This is because loneliness may entail maladaptive cognitions concerning other people and their intentions. Studies across phylogeny, underscore that loneliness is associated with increased awareness of social cues of potential rejection ( 32 , 87 , 88 ) and may be associated in reduced perceptions of social support after trauma ( 56 ). Applied to this study, it may be suggested that ex-POWs suffer from more PTSS than non-combatants, which is a burden by its own merit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because loneliness may entail maladaptive cognitions concerning other people and their intentions. Studies across phylogeny, underscore that loneliness is associated with increased awareness of social cues of potential rejection ( 32 , 87 , 88 ) and may be associated in reduced perceptions of social support after trauma ( 56 ). Applied to this study, it may be suggested that ex-POWs suffer from more PTSS than non-combatants, which is a burden by its own merit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, not only is the POWs’ trauma typically considered to be more severe than that of non-captive combat veterans but due to the interpersonal aspects of captivity ex-POWs are also susceptible to additional interpersonal impediments, particularly insecure attachment orientations and loneliness ( 53 55 ). Similarly, recent research among incarcerated populations has indicated that past traumas may be implicated in more loneliness and less perceived social support ( 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of convergent validity is to assess whether the scales are significantly related as predicted [32]. The UCLA Loneliness Scale was used to assess convergent validity as past research has demonstrated significant positive associations between depressive symptoms, minority stress and loneliness [33,34]; and a significant negative association between social support and loneliness [35]. Loneliness was assessed using the UCLA Loneliness Scale [36], an 8-item validated scale that measures various aspects of loneliness on a 4-point Likert scale ranging from 1 "Never" to 4 "Often".…”
Section: Convergent Validitymentioning
confidence: 99%
“…The purpose of convergent validity is to assess whether the scales are signi cantly related as predicted [32]. The UCLA Loneliness Scale was used to assess convergent validity as past research has demonstrated signi cant positive associations between depressive symptoms, minority stress and loneliness [33,34]; and a signi cant negative association between social support and loneliness [35]. Loneliness was assessed using the UCLA Loneliness Scale [36], an 8-item validated scale that measures various aspects of loneliness on a 4-point Likert scale ranging from 1 "Never" to 4 "Often".…”
Section: Measures To Assess Construct Validitymentioning
confidence: 99%